Entre filólogos y misioneros: debates y usos del quichua en Ecuador (1868-1913) [Estudios] - Vizuete Marcillo, Luis Esteban (2023)
The article focuses on the uses that militant Catholics in Ecuador made of Quichua during the reformation of Catholicism and in the midst of disputes with liberal circles. The printed and manuscript production in Quichua and its production contexts are analyzed. Documents such as the Redemptorist chronicles are also studied, as they allow us to understand the uses and missionary practices. This material had not been historically analyzed so far. The article also presents an overview of the pluralistic visions of Catholics about Quichua and closes with the antiquichuist pastoral turn led by Federico Gonzalez Suarez, at the beginning of the 20th century.